Pengaruh Penyiraman Yang Tepat Pada pertumbuhan Tanaman Kacang Tanah (Arachis Hypogaea L.) - Destini Friska Bestari Waruwu; Sri Oktafiyanti Lombu; Lince Febryani Waruwu; Windi Syahputri Mawar Waruwu; Cynthia Florentina Mendrofa; Yoel Melsaro Larosa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Peanuts (Arachis hypogaea L.) are food crops that have high economic value due to their high nutritional content, especially protein and fat. The purpose of this study is to ensure that the accuracy of watering plants, especially peanut plants, must be truly considered in order to maintain optimal plant growth and development. The research method used is field work practice by cultivating peanut plants directly in Dahan Tabaloho Village, Gunungsitoli District. From the research conducted, it was proven that the effect of accuracy in watering peanut plants greatly affects the growth and development of these plants. When the accuracy in watering is not optimal, it will interfere with the growth of peanut plants.